Evaluasi Kebijakan Penanganan Covid-19 Terhadap Pekerja Konstruksi Gedung di Yogyakarta: The Evaluation of the Covid-19 Handling Policy for Building Construction Workers in Yogyakarta - Rachmad Hidayat; Andreas Triwiyono; Muslikh Muslikh (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2024)
In 2020, the Corona virus or Covid-19 was declared a global pandemic by the World Health Organization (WHO). This virus significantly affected and disrupted the activities of society, including the construction sector. In response to this situation, the Minister of Public Works and Public Housing (PUPR) issued a policy in Ministerial Instruction No. 02 of 2020 regarding the protocol for the prevention of the spread of the Corona Virus Disease 2019 (Covid-19) in the implementation of construction services. The purpose of this research was to measure the effectiveness level of the policy that had been established and to identify the factors influencing the compliance level of construction workers with the Covid-19 prevention policy. Data was collected from construction projects in the Special Region of Yogyakarta province through offline means using the Likert scale. The data was subsequently analyzed using SPSS and SmartPLS for the Structural Equation Modeling (SEM) method. The results indicated that the Ministerial Instruction No. 02 of 2020 issued by the Minister of PUPR had been effectively implemented throughout 2021 and 2022. It was also revealed that certain factors directly and significantly influenced workers' compliance. These factors included workers' understanding and the availability of facilities and infrastructure, with calculated t-values exceeding 1.960 and p-values less than 0.05.